Evaluation of Thymus pseudopulegioides plant extracts for total phenolic contents, antioxidant and antimicrobial properties - GÜL, Latife Betül; ÖZDEMİR, Nilgün; GÜL, Osman; ÇON, Ahmet (International Society of Academicians, 2022)
In this study, the ethanolic extracts of leaf and flower of Thymus pseudopulegioides Klokov & Des. Shost collected from Sultan Murat Plateau of Trabzon, Turkey was assessed for total phenolic contents and antioxidant activities. In addition, antibacterial activity of extracts against nine different bacterial strains (Staphylococcus aureus, Escherichia coli, Pseudomanas aeruginosa, Bacillus cereus, B. pumilus, B. subtilis, B. licheniformis, Listeria innocua and L. monocytogenes) were determined using the agar-dilution method. The extraction yields from leaf and flower were obtained as 10.95% and 0.94% (w/w), respectively. The total phenolic contents of leaf and flower extracts were determined as 7.84 and 0.39 mg GAE/g, respectively. Antioxidant activities of the ethanolic extracts from leaf and flower were evaluated by using DPPH radical scavenging, and leaf extract showed better antioxidant activity than flower extract. Although, minimum inhibitory concentration (MIC) of leaf extracts was determined as 1.028 mg/mL for all bacteria except B. subtilis (0.256 mg/mL), MIC of flower extracts for B. subtilis and B. pumilis was found as 0.256 mg/mL and for others was 0.512 mg/mL. The extracts of the tested parts of Thymus pseudopulegioides, especially the leaves might be valuable for functional food and therapeutic applications.
Keywords: Antimicrobial activity; Antioxidant activity; total phenolic; Thymus pseudopulegioides; Food Engineering; Gıda Mühendisliği; 3. Good health